Les imprimés et l'Amérique en France pendant les guerres de Religion - Oury Goldman (Nuevo mundo - Mundos Nuevos, 2013)
Contrary to a prevalent historiographical perspective, sixteenth century France was indifferent to information coming from the “New Worlds”. Nevertheless, the use and production of printed works on America have had a singular history in the French speaking world, characterized by debates and confrontations coming from the French Wars of Religion. This paper aims to explore some of the uses of the American subject by humanists, protestant and “Politiques” thinkers, and shows their interaction with religious and political contemporary debates. It is important to understand how information on the “Savages”, when confronted to information on the “Ancients” and the “Moderns”, allowed to renew their questioning of the legitimacy of violence, the limits of political authority and even History's direction. However, to go beyond the idea of a simple strategic use of information coming from America by the authors examined, the paper tries to demonstrate how this context changed as much the contemporaries' own norms than the way the New Worlds were considered in itself.